Pin-up girl [videorecording (DVD)] - Humberstone, H. Bruce, 1901-1984; Grable, Betty, 1916-1973; Harvey, John; Raye, Martha; Block, Libbie (20th Century Fox Home Entertainment, 2006)
Lorrie Jones visits a popular hangout for servicemen. She falls in love with a war hero and tries to come up with a way to be near him. Lorrie pretends to be a Broadway star, and in turn she is hired by the USO and becomes a real star.